Sugarcane genetic resistance against holoparasitic angiosperm Aeginetia pedunculata (Orobanchaceae) - MRINAL KANTI DASGUPTA2, BIKASH RANJAN RAY1* and (Indian Phytopathology, 2012)
Twenty eight sugarcane genotypes were screened against the total root parasitic angiosperm Aeginetia pedunculata (Orobanchaceae) by root inoculation with parasite seed. All the entries tested showed parasitization and wilt but variations were observed in respect of first flowering, growing degree days (GDD), area under Aeginetia progress curve (AUAPC) of the parasite and wilting of cane. Breeding of sugarcane by making crosses involving NCo 310 (resistant to A. indica) as either male or female parent resulted in development of genotypes susceptible to A. pedunculata.